Evaluation of telecommunications regulatory practice in the Kingdom of Bahrain: development and challenges. (21st June 2019) - Al-Alawi, Adel Ismail; Al-Bassam, Sara Abdulrahman
This study has investigated the evaluation of Telecommunications Regulatory Authority (TRA) practice in the Kingdom of Bahrain. Having realised the importance of telecommunication, Bahrain has become one of the leading information and communication technologies (ICT) economies in the Gulf Cooperation Council (GCC) region and is ranked among the top 30 in the world. Such a ranking has encouraged the researchers to take Bahrain's TRA as the focus of this study. The aim of this paper is to evaluate and identify the factors that have influenced the TRA framework in the Kingdom and to investigate the development and challenges of TRA in Bahrain and how to lead to the best performance in the market place. The study also investigated the role of certain factors in telecommunication regulation. Interviews and surveys with the TRA and major operators in Bahrain were conducted. The findings show that licensing, interconnection, price regulation, competition policy and universality access are key factors influencing the telecommunication regulatory framework in Bahrain.